Article Review: Identification of Secondary Metabolites Using the TLC-Densitometry Method - Rizki Annisa Ramadhani; Hilmia Mufida; Yola Asri Paramitha; Muhammad Zaki Hamzah; Neza Ardelia Putri; Neysa Husna Luthfiyah; Zahra Putri Ramadhani; Dini Indriyanti (INDOGENIUS, 2026)
Background & Objective: This review article discusses the identification and quantification of secondary metabolites using densitometric thin-layer chromatography (TLC) based on 24 journal articles published over the past ten years. The compounds analyzed include quercetin, catechins and their derivatives (EGCG), phenolic compounds, flavonoids, and various other secondary metabolites. Method: Based on the overall data, densitometric TLC is an effective method for the identification and quantification of secondary metabolites because it provides good separation, clear Rf values, and stable quantification results across various natural material matrices. Result: The results of the study indicate that silica gel 60 F254 and GF254 are the most commonly used stationary phases, while variations in the mobile phase are the primary factors influencing Rf values and separation resolution. In the quercetin group, Rf values ranged from 0.26 to 0.89, with the highest concentration in meniran at 3.5% and the lowest in cocoa beans at 0.115%. Conclusion: Analysis of catechins showed Rf values ranging from 0.22 to 0.60, with the highest content in avocado seeds at 25.55% and gambir at 25.50%, while EGCG in green tea had an Rf value of 0.21 and a content of 3.33%. Phenolic and flavonoid compounds exhibited Rf values ranging from 0.24 to 0.94, influenced by differences in polarity and solvent composition. Other secondary metabolites such as syringic acid, kaempferol, chlorogenic acid, eugenol, beta-sitosterol, oleanolic acid, ursolic acid, myricetin, and rutin exhibited migration patterns consistent with their chemical properties.